Analisis Etika Penyebaran Hoaks di Media Sosial dalam Perspektif Teknologi Informasi - Amany Rafa Lihardi; Evy Nurmiati; Elvi Fetrina (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2026)
The development of information technology and social media has accelerated the spread of information in society. However, this convenience has also increased the spread of hoaxes and misinformation in digital spaces. The rapid circulation of unverified information may trigger social conflict, reduce public trust, and influence users’ psychological conditions. This study aims to analyze the spread of hoaxes on social media from the perspective of information technology ethics. The research employed a descriptive qualitative method with a literature review approach by collecting data from scientific journals, proceedings, books, and other relevant academic sources related to hoaxes, misinformation, digital literacy, and social media ethics. Data were analyzed using content analysis techniques to identify the causes, impacts, and prevention efforts related to the spread of hoaxes on social media. The findings indicate that low digital literacy, cognitive bias, Fear of Missing Out (FOMO), and social media algorithms are the main factors contributing to the spread of misinformation in digital environments. In addition, recommendation systems on social media strengthen echo chamber and filter bubble phenomena, making users more vulnerable to unverified information. From the perspective of information technology ethics, spreading hoaxes contradicts the principles of honesty, responsibility, and truthfulness in digital communication. Therefore, improving digital literacy, critical thinking skills, and ethical awareness in social media use is necessary to create a healthier and more responsible digital environment.